PROBLEMS AND STRATEGIES FOR FORMING ACADEMIC INTEGRITY CULTURE AMONG SCHOOL STUDENTS - S. Artikova (American Journals Publishing, 2026)
This paper focuses on the problems and strategies related to the formation of academic integrity culture among school students. It analyzes the main factors that hinder the development of academic honesty, such as lack of awareness, insufficient ethical education, and improper assessment practices. The study emphasizes the importance of fostering moral values, responsibility, and independent thinking in students from an early age. Effective strategies, including educational interventions, teacher guidance, fair assessment systems, and the integration of academic ethics into the learning process, are discussed. The findings highlight that developing a sustainable culture of academic integrity plays a crucial role in improving the overall quality of education and preparing students for responsible academic and professional life.
Keywords: Academic integrity, school students, ethical education, academic honesty, educational strategies.